Pengaruh Hubungan Keluarga Dan Lingkungan Sosial Terhadap Pencegahan Penggunaan Napza Pada Remaja Di Kecamatan Kuta Baro Aceh Besar - Dewi Sartika; Iskandar Iskandar (Universitas Katolik Widya Karya Malang, 2023)
Efforts to prevent drug abuse will be able to live with the encouragement of parents. The Center on Addiction and Substance Abuse (CASA) suggests that key families to prevent drug addiction, and the social environment, provide ethical, moral and counseling, teaching and training according to adolescent self-development. The purpose of research to determine the influence of family and social relationships against drug abuse prevention in Kuta Baro Aceh Besar. Correlative research design with cross-sectional approach. The number of samples is 68 respondents. The result of univariate research shows that as many as 54,4% respondent with family is not harmonic, 52,9% respondent with negative social environment, 51,5% respondent with negative drug abuse prevention. Bivariate results show that there is a family relationship with the action of prevention of drug abuse in Cot Yang District of Aceh Besar Regency with P value = 0,031 and there is social environment relation with the action of prevention of drug abuse in Gampong Cot Yang Sub-district of Aceh Besar Regency with p value = 0.035. It is suggested that the Geuchik Gampong can work together with religious leaders and youth of the village to provide information for adolescents about the dangers of abuse.